Investigação das habilidades e conhecimentos mobilizados na resolução de questões da segunda fase da Olimpiada Brasileira de Matemática das escolas públicas - OBMEP - Dias, Alana Moreira (Universidade Federal do Tocantins, 2025)
The second phase of the OBMEP represents a significant challenge for students, especially due to the essay-like nature of its questions. In this context, this Final Course Work was designed with the objective of identifying and analyzing the mathematical skills and knowledge present in the questions of the second phase of the Brazilian Mathematics Olympiad for Public Schools (OBMEP), held annually by the federal government since 2005. The research assumes a qualitative descriptive nature and had as its object of study the questions of the second phase of the OBMEP held in 2023 for levels 1 and 2 applied to students in the second segment of elementary school. These were analyzed, observing in particular the mathematical skills and knowledge necessary for their correct development, in addition to the possible difficulties encountered by the student during the resolution. Throughout the chapters, information about the Olympiad, the theoretical basis adopted, the methodological procedures employed, the interpretations made and the results obtained are presented.